Challenging the Egoistic Paradigm - Bowie, Norman E. (Business ethics quarterly, 1991)
Most economists are committed to some version of egoism. After distinguishing among the various sorts of egoistic claims, I cite the empirical literature against psychological egoism and show that attempts to account for this data make these economists’ previous empirical claims tautological. Moreover, the assumption of egoism has undesirable consequences, especially for students; if people believe that others behave egoistically, they are more likely to behave egoistically themselves. As an alternative to egoism I recommend the commitment model of Robert Frank.The equivalent of egoism at the organizational level is that business firms seek (should seek) to maximize profits. I present arguments to show that a conscious attempt by managers to maximize profits is likely to fail. A committed altruism is more likely to raise profits. I suggest that a firm should take as its primary purpose providing meaningful work for employees.